Flood disaster management of Hat Yai City Municipal Hat Yai District Songkhla Province - นราแหวว หทัยทิพย์; กมลเวชช ทวิดา (Journal of Politics and Governance, 2018)
This is a mixed methods research which integrates qualitative and quantitative research designs two purposes of this research are studying factor of the successful flooding management of Hat Yai Municipal Community and providing an advice for improving flood disaster management in the similar condition. The research used in-depth interview to collect data from 18 people who involved in flooding management, Moreover, the researcher used questionnaires to collect information from 400 respondents who live in the study area. Frequency, percentage, mean, standard deviation and observation were used as research in statistical methods to analyze and understand the data combined with documentary research. The study shows the factors of successful community participation in the management of disaster (Hat Yai Model). The first factor is the integration between public organizations. Second the mean of community integration is in a high level at 4.03. Third is the knowledge of water management. Forth, the percentage of an effective disaster warning is in a high level at 96.83 Last, the effective of Ban Phi Lieng project which is a community independence model. The conclusion from this research shows that the most important factor of, “Hat Yai model” is the integration of every community sectors.